LEAN PRODUCTION SYSTEM AS AN APPROACH TO DIGITALIZATION IN SIEMENS LTD. – ARABIA ELECTRIC LTD. - Karningsih, P.D.; Narvas, M. F.; Young, M.N. (Journal of Advanced Manufacturing Technology (JAMT), 2024)
In order to stay competitive in the global market, continuous improvement in all aspects of operations is essential. Due to the need for fast responses to market changes and an ongoing search for a sustainable future, the constraints of information flow among stakeholders become very critical. A global powerhouse company - workshop is facing this issue, which causes activity delays that are considered non-value-adding operations and results in additional costs. Digital technology has been acknowledged for eliminating non-value-adding operations. Digitalization generally requires huge capital investment. However, there is an opportunity to start digital transformation by utilizing existing platforms and applications. This study aims to develop a new framework to assist the company in digital transformation in a cost-effective manner. The proposed framework consists of six modules: identifying the technologies to adapt, categorizing the operations, assessing potential risks, measuring environmental impacts, identifying the advantages, and implementing change management procedures, profitability assessment, and corporate social responsibility programs. The proposed framework was then applied in a global powerhouse company - workshop based on a case study. The results show a significant reduction in time due to the elimination of non-value-added activity (delay). Another tangible benefit is the reduction or even elimination of consumption of bond papers by up to 98% or 100%, contributing to the conservation of natural resources and minimizing environmental impact. Further savings of 100% are contributed by the elimination of paper storage and the reduction of service fees for printers.